2015
DOI: 10.1111/ecc.12289
|View full text |Cite
|
Sign up to set email alerts
|

Do the elderly raise different issues when using the Patient Concerns Inventory in routine head and neck cancer follow-up clinics?

Abstract: Head and Neck (H&N) cancer treatment can have a major detrimental impact on patient lives, and these issues can go unrecognised and be inadequately addressed. The aim of this paper is to compare the Patient Concerns Inventory (PCI) responses across age groups attending routine H&N cancer follow-up clinics with particular focus on the elderly (75 years or older). The PCI-HN data were obtained from patients attending follow-up clinics between August 2007 and January 2013. The groups for comparison were: <55 (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…Patients indicated that they were reluctant to discuss emotions with a doctor or nurse. This reluctance is consistent with previous studies that showed that patients more often select medical topics from preparation tools than psychosocial and practical topics (Ghazali et al, ; Rogers, Audisio, & Lowe, ). This result may also explain the lack of effects of (the use of) concern lists on the discussion of concerns during consultations (Farrell et al, ; Hill et al, ) or why concerns in general are discussed to a lesser extent in consultations than information needs (Jansen et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…Patients indicated that they were reluctant to discuss emotions with a doctor or nurse. This reluctance is consistent with previous studies that showed that patients more often select medical topics from preparation tools than psychosocial and practical topics (Ghazali et al, ; Rogers, Audisio, & Lowe, ). This result may also explain the lack of effects of (the use of) concern lists on the discussion of concerns during consultations (Farrell et al, ; Hill et al, ) or why concerns in general are discussed to a lesser extent in consultations than information needs (Jansen et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…In breast cancer it has been suggested that perceiving cancer as more threatening facilitates PTG . While information on perceived threat of HNC by age is lacking, younger survivors more often report fear of recurrence as their greatest concern . Bellizzi suggested that younger survivors of traumatic events experience more growth because they realize they have more time left to accomplish desired goals, whereas older survivors reach a peaceful acceptance about their life situation.…”
Section: Discussionmentioning
confidence: 99%
“…These include eating and speech difficulties, facial disfigurement, and elevated distress, which have marked negative effects on survivors' QoL following treatment . Fear of recurrence (FoR) can also be a persistent and significant issue in this population, with noted deleterious effects on QoL; FoR is the most frequently cited concern by HNC survivors aged less than 70 years old . Our recent qualitative research has illustrated the variety of strategies that HNC survivors use to self‐manage these ongoing issues, the barriers they encounter in their self‐management attempts, and the processes through which they integrate self‐management into their daily lives .…”
Section: Introductionmentioning
confidence: 99%